USE OF DEMONSTRATION METHOD IN IMPOVING STUDENT’S LEARNING ACHIEMENT IN CLASS IV SDK NDETUNDORA 3 IN THE SUBJECT OF SOCIAL SCIENCES - Anselmus Mema; Maria Mikhaela Peten Tukan (Media Inovasi Pendidikan dan Publikasi, 2024)
This study discusses the use of demonstration methods in the study of Social Sciences. This study is motivated by the low learning outcomes of many factors, especially the factors of teachers and students. The teacher as an important component in the teaching and learning process has a very strategic role in the effort to stablish quality human resources. The low learning outcomes of social studies are following several studies. Thus, learning using demonstration methods can improve learning outcomes, activeness, and motivation forstudents. The responsibility of students towards the task is quite high and helps students to be actively involved in learning activities.